2010
DOI: 10.1363/4211710
|View full text |Cite
|
Sign up to set email alerts
|

“We're the Heroes!”: Fathers' Perspectives on Their Role In Protecting Their Preteenage Children from Sexual Risk

Abstract: Research and interventions concerning parent-child communication about sex should not neglect the role of fathers. However, some fathers may need support to overcome barriers to effective communication, especially with their daughters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
56
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 24 publications
5
56
0
Order By: Relevance
“…On the other hand, boys are given more messages suggesting that they should use condoms (Fasula et al, 2007) and warnings about getting a girl pregnant (DiIorio et al, 2006). These findings emerging from qualitative analyses reflect prominent gendered sexual scripts that are more restrictive toward girls and more accepting or permissive toward boys (Averett, Benson, & Vaillancourt, 2008;Hussen, Bowleg, Sangaramoorthy, & Malebranche, 2012;Wilson et al, 2010). Together, results from qualitative studies highlight the importance of considering the gender-specific tone and content of sexual messages, particularly those provided by parents.…”
Section: Limitation Two: Minimal Analyses Of Specific Sexual Themes Cmentioning
confidence: 87%
See 2 more Smart Citations
“…On the other hand, boys are given more messages suggesting that they should use condoms (Fasula et al, 2007) and warnings about getting a girl pregnant (DiIorio et al, 2006). These findings emerging from qualitative analyses reflect prominent gendered sexual scripts that are more restrictive toward girls and more accepting or permissive toward boys (Averett, Benson, & Vaillancourt, 2008;Hussen, Bowleg, Sangaramoorthy, & Malebranche, 2012;Wilson et al, 2010). Together, results from qualitative studies highlight the importance of considering the gender-specific tone and content of sexual messages, particularly those provided by parents.…”
Section: Limitation Two: Minimal Analyses Of Specific Sexual Themes Cmentioning
confidence: 87%
“…For example, both messages promoting abstinence and those encouraging sexual exploration may be perceived by research participants as ''communication about sexual intercourse.'' Moreover, findings from qualitative research demonstrate that African American parents discuss a range of complex issues with their youth, including avoiding the negative consequences of sex, as already noted, as well as the importance of self-respect, the meaning of healthy sexuality, and the negative influence of media models (e.g., Akers et al, 2011;DiIorio et al, 2006;Wilson, Dalberth, & Koo, 2010). These themes are seldom included in the topic approach but may figure prominently in formative communications.…”
Section: Limitation Two: Minimal Analyses Of Specific Sexual Themes Cmentioning
confidence: 94%
See 1 more Smart Citation
“…Moreover, promoting personal responsibility for sexual health is discordant with paternalistic values in a traditionally familistic framework. Instead, restrictive parenting practices serve the goal of protecting and limiting sexuality to marriage (Raffaelli & Ontai, 2001;Wilson, Dalberth, & Koo, 2010). However, recent research has shown that Latino parents have become more realistic about expectations for abstinence, particularly because of the postponement of marriage for college during emerging adulthood (Guilamo-Ramos, Jaccard, Dittus, & Collins, 2008).…”
Section: Discourses About Sex Among Latino Parentsmentioning
confidence: 99%
“…First, it has a heteronormative assumption that the future partners of boys will ultimately, forever and always be women when in reality many males have sex with other men. Secondly, it reinforces the patriarchal (traditional) idea that males have an obligation to protect females from sexual risks (Mara, 2010;Wilson, Dalberth & Koo, 2010).…”
Section: Msm Largely Ignoredmentioning
confidence: 64%